2021
DOI: 10.2147/jir.s302934
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba Extract 50 (GBE50) Ameliorates Insulin Resistance, Hepatic Steatosis and Liver Injury in High Fat Diet-Fed Mice

Abstract: Background: Ginkgo biloba extract 50 (GBE50) has a variety of pharmacological functions such as anti-inflammatory, antioxidant and maintenance of glucose and lipid metabolism homeostasis. However, the therapeutic effects and mechanisms of GBE50 on non-alcoholic fatty liver disease (NAFLD) remain unknown. Therefore, in this study, we evaluated the therapeutic effects of GBE50 in NAFLD by using a high-fat diet (HFD) mice model. Methods: C57BL/6J mice were fed a HFD diet for 15 weeks and were given respectively 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
(87 reference statements)
1
14
0
Order By: Relevance
“…Hepatic steatosis is promoted by the abnormal deposition of saturated FAs, such as CHO and TG, and the constant accumulation of saturated FAs promotes the progression of liver inflammation and NAFLD. ALT and AST are important markers for evaluating liver damage, and ALT is a more specific marker of hepatic injury than AST [24][25][26]. We found that TG and ALT levels in the control group were significantly higher than that in the WKY group at the beginning of the experiment.…”
Section: Discussionmentioning
confidence: 66%
“…Hepatic steatosis is promoted by the abnormal deposition of saturated FAs, such as CHO and TG, and the constant accumulation of saturated FAs promotes the progression of liver inflammation and NAFLD. ALT and AST are important markers for evaluating liver damage, and ALT is a more specific marker of hepatic injury than AST [24][25][26]. We found that TG and ALT levels in the control group were significantly higher than that in the WKY group at the beginning of the experiment.…”
Section: Discussionmentioning
confidence: 66%
“…It has been shown that high flavonoid and phenolic compound in ginkgo biloba extracts exhibited an elimination of lipid synthesis and liver secretion in non-alcoholic fatty liver disease via ameliorating endoplasmic reticulum stress signals activation. 34 Indeed, clinical parameters of hepatic profiles characterized the damage in liver such as hepatocyte inflammation, oxidative stress, and liver injury. 35 Therefore, we can assume that GBR exhibits an anti-inflammatory activity via preserving liver function.…”
Section: Discussionmentioning
confidence: 99%
“…[ 87 ] EGb 50 is a concentrated extract of G. biloba leaves containing 6.4% ginkgolides, 26.4% flavonoid glycosides, and 44.1% total flavonoids. [ 88 ] EGb 761, comprising 24% flavonoid glycosides and 6% terpenoids, inhibited platelet activation, removed free radicals, and mitigated p53‐mediated and mitochondrion‐dependent proapoptotic effects doxorubicin‐induced cardiac toxicity. [ 89 ] EGb 50 also exerted beneficial effects against myocardial ischemia–reperfusion (IR) by reducing the oxidative stress in the reperfused myocardium and increasing immunity and antioxidant activities in IR rats.…”
Section: G Biloba and Covid‐19mentioning
confidence: 99%